Advances in communications satellite systems: proceedings of the 36th International Communications Satellite Systems Conference (ICSSC-2018) - Otung, Ifiok; Butash, Thomas; Garland, Peter (IET telecommunications series, 2019)
The International Communications Satellite Systems Conference (ICSSC) is one of the most influential technical conferences in the field. The 36th edition was held in October 2018 in Niagara Falls, Canada. These proceedings present a broad spectrum of space communications topics from the conference, from the evolution of GEO from traditional area coverage to Ultra High Throughput Satellites (UHTS), the growing number of mega constellations expected to enter service in the next decade, navigation applications such as vehicle autonomy, wideband data backhaul from scientific and remote sensing payloads in LEO, and the extension of the 5G network to near earth, lunar and deep space environments in support of human exploration.